2019
DOI: 10.1088/1742-6596/1334/1/012012
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of complex of lysine dendrimer of 2nd generation with molecules of therapeutic KED peptide by computer simulation

Abstract: Lysine dendrimers could be used in many biomedical applications. For example these dendrimers could be used for delivery of short regulatory peptides consisting of several aminoacid residues. We investigated earlier interactions between lysine dendrigraft of 2nd generation and molecules of KED peptide. In present paper we study interaction of lysine dendrimer and molecules of KED peptide. The system containing one dendrimer of 2nd generation and 8 molecules of KED in water with explicit account of counterions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The interactions of these oligopeptides can benefit from the various protons that can be exchanged in the structure and thus lead to better interaction energies, as has been described in previous studies. 47 In previously reported theoretical-experimental studies with dendrimers of different natures, it was shown that the interaction with some peptides is stronger in the periphery, 63,64 given the large number of functional groups that give rise to a stable complex. 64 This opens a wide range of possibilities for using a PAMAM dendrimer as a base with high affinity towards different amino acids for the separation of peptides encrypted in a protein hydrolysate.…”
Section: Ft-ir Experimental Study: Pamam Dendrimers Pamam-amino Acidsmentioning
confidence: 99%
“…The interactions of these oligopeptides can benefit from the various protons that can be exchanged in the structure and thus lead to better interaction energies, as has been described in previous studies. 47 In previously reported theoretical-experimental studies with dendrimers of different natures, it was shown that the interaction with some peptides is stronger in the periphery, 63,64 given the large number of functional groups that give rise to a stable complex. 64 This opens a wide range of possibilities for using a PAMAM dendrimer as a base with high affinity towards different amino acids for the separation of peptides encrypted in a protein hydrolysate.…”
Section: Ft-ir Experimental Study: Pamam Dendrimers Pamam-amino Acidsmentioning
confidence: 99%